Phylogenetic relationships of the macaques (cercopithecidae Macaca) inferred from partial mitochondrial dna (mtDNA) cytochrome oxidase II (coii) gene - Noor Aisyah, Binti A Rahim (Universiti Malaysia Sarawak, UNIMAS, 2013)
The molecular phylogenetic relationships among ten species of macaques were assessed using mitochondrial DNA (mtDNA) cytochrome oxidase II (COII) gene. The 24 individuals of ten species within genus Macaca (M. sylvanus, M. mulatta, M. cyclopis, M. arctoides, M. fascicularis, M. assamensis, M. thibetana, M. nemestrina, M. leonina and M. silenus) are used in this study. A Trachypithecus obscurus and a Pongo pygmaeus was used as the outgroup. The phylogenetic trees were constructed using neighbor-joining (NJ), maximum parsimony (MP) and maximum likelihood (ML) methods. The maximum parsimony bootstrap proportions that obtained are lower than those from earlier studies based on the COII gene. The tree produced shows concordant topology that produced five distinct groups where the M. sylvanus as sister clade to all Asian macaques and the mulatta group, the sinica group and the silenus group formed their own monophyletic clade. Meanwhile, the fascicularis group formed a paraphyletic assemblage in the tree.